PEMANFAATAN LAYANAN PERSALINAN DI PUSKESMAS DI KABUPATEN BANTUL - , Atthobari; , dr. Mubasysyir Hasanbasri, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Since the introduction of the concept of community health centers in 1968, a variety of results has been made. The maternal mortality rate and infant mortality has fallen and while it figures out the average life expectancy of Indonesia has increased significantly. One strategic consideration is the construction of health centers to equalize health services closer to the group of health care facilities are needed in rural areas, one of which is service delivery. The growth of private health care in Bantul was encouraging even showed a significant growth rate, so that the health services are generally dominated by private health care units. The phenomenon of people's perception of the utilization of health services is an interesting problem to be studied. People's perception of the quality of health care provided health services can be used as a reference for the development of health services in the direction of a better. Objective : This study aims to describe the utilization of obstetric care at the health center in Bantul, and the factors that influence the utilization of obstetric care at the health centers. Methods : This study is a case study design using qualitative methods. Data collection methods used were in-depth interviews to get deeper or wider than maternal, community leaders and village heads. Analysis of the data using analysis nonstatistik according to descriptive narrative research. Results : Service delivery in health centers utilized by 4.6% maternal, or 19 of 407 maternal health center in the region Pandak I during 2011. The rest use the service delivery in private practice midwives, maternity homes or in hospitals. Conclusion : Utilization of service delivery has not been evenly distributed to all health centers in the region working population and is concentrated on the population residing closer than health centers. Health Center can not meet the needs of service delivery to the community health centers that have not been given a good image, especially relating to the skills that are lacking personnel, facilities that are less comprehensive services and quality medicines are low.